Repetitive transcranial magnetic stimulation for Alzheimer’s disease: an overview of systematic reviews and meta-analysis - Xue, Hua; Li, Ya-xin; Xiao, Ya-song; Fan, Wen-hui; He, Hong-xian (Frontiers in Aging Neuroscience, 2024)
Objective Alzheimer’s disease (AD) is a prevalent neurodegenerative condition that significantly impacts both individuals and society. This study aims to evaluate the effectiveness of repetitive transcranial magnetic stimulation (rTMS) as a treatment for AD by summarizing the evidence from systematic reviews (SRs) and meta-analyses (MAs). Methods SRs/MAs of rTMS for AD were collected by searching Embase, Web of Science, Cochrane Library, PubMed, CNKI, VIP, Sino-Med, and Wanfang databases. The search was conducted from database creation to January 23, 2024. Methodological quality, reporting quality and risk of bias were assessed using the Assessing Methodological Quality of Systematic Reviews 2 (AMSTAR-2), Risk of Bias in Systematic Reviews (ROBIS) tool and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). In addition, the quality of evidence for outcome measures was assessed using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE). Results Eight SRs/MAs included in this study met the inclusion criteria. Based on the AMSTAR-2, 4 of the SRs/MA were classified as low quality, while the remaining 4 were deemed to be of very low quality. The PRISMA analysis revealed that out of the 27 items reporting, 16 achieved full reporting (100%). However, there were still some deficiencies in reporting, particularly related to protocol and registration, search strategy, risk of bias, and additional analysis. The ROBIS tool indicated that only 3 SRs/MAs had a low risk of bias. The GRADE assessment indicated that 6 outcomes were of moderate quality (18.75%), 16 were of low quality (50%), and 10 were classified as very low quality (31.25%). Conclusion Based on the evidence collected, rTMS appears to be effective in improving cognitive function in AD patients, although the methodological quality of the SRs/MAs reduces the reliability of the conclusions and the overall quality is low. However, based on the available results, we still support the value of rTMS as an intervention to improve cognitive function in AD. In future studies, it is necessary to confirm the efficacy of rTMS in AD patients and provide more reliable and scientific data to contribute to evidence-based medicine.